The occurrence and comparative analysis of bacterial vaginosis and its association with urinary tract infections among pregnant women in a tertiary care hospital of Western Uttar Pradesh - Khilika Sethi; Naila Begum; Aysha Aymen (Microbiologia Medica)
Background: Bacterial Vaginosis (BV) is the most prevalent etiology of vaginal discharge in women of reproductive age. It is characterized by a shift in the vaginal microbiota, where Lactobacillus species are diminished and replaced by a diverse array of anaerobic bacteria. BV is associated with adverse pregnancy outcomes, including preterm labor and low birth weight, as well as an increased susceptibility to Urinary Tract Infections (UTIs). As such, it represents a significant public health concern. The diagnosis of bacterial vaginosis is typically established through the application of Amsel's criteria and the Nugent scoring system.